Salam Arabic Application Development - johar, Nur Sabrina; Murli, Norhanifah (Applied Information Technology And Computer Science, 2022)
Arabic Language subject is an elective subject which exists in Malaysia Education System to give a chance for the student to learn foreign language besides Malay and English languages. The student who wants to learn the Arabic language at school will have the chance to learn from various methods so that they can master the language well such as through speaking, reading, listening, and writing methods. The introduction of learning Arabic is very important to increase the interest for students to learn the Arabic Language. Therefore, this project is to develop Salam Arabic mobile application for a student to help them in mastering the language and help teachers to make this application as one of the learning aids. Salam Arabic Application is a learning application that is developed especially for Form One students who want to learn the Arabic language. This project is developed using the Waterfall model as its methodology because this method is suitable and easy to learn without having any cost. The respondent for this study is a Form One student who learns Arabic Language subject. The respondent from the student is needed to make sure the application has achieved its objective.